Dukungan Sosial dan Perilaku Sehat Guru Inisiator Sekolah Adiwiyata - widyastuti widyastuti; Lely Ika Mariyati; Andriani Eko Prihatiningrum (Pusat Penerbitan Ilmiah Universitas Muhammadiyah Kalimantan Timur, 2019)
Schools have large potential of human resources. Unfortunately, this potential has not effectively supported the Sekolah Adiwiyata program. Two junior high schools in Tulangan Subdistrict, Sidoarjo Regency, have potential human resources that can be optimized in initiating the Sekolah Adiwiyata program. Post-training training and mentoring were provided as a form of social support for the initiation of the Sekolah Adiwiyata program. The results show that social support strengthens the teacher's healthy behavior as the initiator of the Sekolah Adiwiyata.